2015
DOI: 10.1002/jor.22943
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of a novel shoulder contracture mouse model

Abstract: Frozen shoulder is a relatively common disorder that leads to severe pain and stiffness in the shoulder joint. Although this disorder is self-limiting in nature, the symptoms often persist for years, resulting in severe disability. Recent studies using human specimens and animal models have shown distinct changes in the gene expression patterns in frozen shoulder tissue, indicating that novel therapeutic intervention could be achieved by controlling the genes that are potentially involved in the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
4
16
0
Order By: Relevance
“…The current state of knowledge reflects a poor understanding of the etiology and pathologic mechanism for frozen shoulder [7, 8, 14]. Histologically, Ozaki et al [6] and Bunker et al [13] reported that fibrosis of the capsule was the main lesion, but neither inflammation nor synovitis was observed [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current state of knowledge reflects a poor understanding of the etiology and pathologic mechanism for frozen shoulder [7, 8, 14]. Histologically, Ozaki et al [6] and Bunker et al [13] reported that fibrosis of the capsule was the main lesion, but neither inflammation nor synovitis was observed [15].…”
Section: Discussionmentioning
confidence: 99%
“…To date, seven studies describing the development of animal frozen shoulder models using canine, rat, or mouse have been reported [1420]. The optimal choice of animal and methodology that would be most useful in creating a model for frozen shoulder remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten days after the procedure, mice were euthanized by CO 2 overdose to harvest their left shoulders. Immediately following sample collection, passive ROM was measured using the manner reported by Oki et al 33 Then, the samples were fixed in 10% neutral buffered formalin for one day, and were decalcified, dehydrated, and embedded in paraffin wax for histological examination. HE and Masson staining were conducted based on the established method.…”
Section: Shoulder Sample Harvest and Analysismentioning
confidence: 99%